'Sea of blood': the intended and unintended effects of criminalising humanitarian volunteers assisting migrants in distress at sea. Issue 1 (5th October 2021) - Gordon, Eleanor; Larsen, Henrik Kjellmo
Abstract : This paper investigates the impact of the recent criminalisation of humanitarian actors engaged in the search for and rescue of migrants in distress in the Mediterranean Sea, focusing on the impact on the motivation and engagement of humanitarian volunteers in Greece. It argues that criminalisation is aimed at reducing search and rescue (SAR) activities and thus removing perceived 'pull factors' for migrants. The paper locates this phenomenon within the broader trend of policing and punishing those who assist migrants in order to deter them and prevent others from engaging in such endeavours. It finds that efforts to criminalise can have the unintended effects of encouraging and mobilising volunteers, as well as generating public attention and support for migrants. However, the negative consequences of criminalisation are far‐reaching, including contributing to a high mortality rate among those crossing the Mediterranean without SAR capabilities and the heightened risk of violence against migrants and those who help them. نبذة مختصرة: تبحث هذه الورقة في تأثير التجريم الأخير للجهات الإنسانية الفاعلة والمنخرطة في أنشطة البحث والإنقاذ (SAR) للمهاجرين المعرضين للخطر في البحر الأبيض المتوسط ، مع التركيز بشكل خاص على التأثير و على التحفيز وإشراك المتطوعين الإنسانيين في اليونان. نتجادل فيما بيننا بأن التجريم يهدف إلى الحد من أنشطة البحث والإنقاذ وكذلك إزالة "عوامل الجذب" المتصورة لدى المهاجرين. فأننا نضع هذه الظاهرة في الاتجاه الأوسع لضبط ومعاقبة أولئك الذين يساعدون المهاجرين من أجل ردعهم ومنع الآخرين من المشاركة في مثل هذه الأنشطة. نجد أن الجهود المبذولة للتجريم يمكن أن يكون لها آثار غير مقصودة من خلال تحفيز المتطوعين وتعبئتهم ، فضلاً عن جذب اهتمام الجمهور ودعمهم. ومع ذلك ، فإن العواقب السلبية للتجريم بعيدة المدى ، بما في ذلك المساهمة في ارتفاع معدل الوفيات لأولئك الذين يعبرون البحر الأبيض المتوسط بدون قدرات عملية البحث والإنقاذ ، فضلاً عن زيادة مخاطر العنف ضد المهاجرين ومن يساعدهم الكلمات الدالة: تجريم ، متطوعون إنسانيون ، هجرة ، بحث وإنقاذ 摘要: 本文调查了最近从事地中海遇险移民搜救活动（SAR）的人道主义行动者被刑事定罪的影响，特别关注对希腊人道主义志愿者的动机和参与的影响。我们认为，刑事化的目的是减少搜救活动，从而消除对移民的感知 "拉动因素"。我们将这一现象置于对协助移民的人进行监视和惩罚的大趋势中，该趋势阻止他们并防止其他人从事此类活动。本文发现，通过激励和动员志愿者，以及引起公众对他们的关注和支持，刑事化的努力可以产生意想不到的效果。然而，刑事化亦具有深远的消极影响，包括导致在没有搜救（SAR）条件下穿越地中海的移民的高死亡率，以及使得针对移民和为移民提供帮助者的暴力风险的增加。 关键词：刑事化，人道主义志愿者，移民，搜索和救援